2014
DOI: 10.1108/lr-12-2013-0163
|View full text |Cite
|
Sign up to set email alerts
|

In transition: academic e-book reading in an institution without e-books

Abstract: The paper reports the results of a study that examined the ways in which graduate-level library and information science students make use of e-books and e-readers at an institution that does not offer e-books through its library. The study used three research methods-a survey, focus groups, and interviews-to investigate library and information science students' reading habits and preferences. The findings suggest that despite the barriers of access and usability, the students have generally incorporated e-book… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…This finding is not surprising as work demands had been previously found to influence information behavior (Ingwersen and Jarvelin, 2005;Vakkari, 2003;Yuelin and Belkin, 2008). In the context of professional reading, while many participants have adapted to reading digitally, the majority of them prefer to read longer professional documents in print, a preference prevalent in previous studies (Lopatovska et al, 2014;Zhang and Kudva, 2013;Woody et al, 2010).…”
Section: Effects Of Demographic and Institutional Characteristics On mentioning
confidence: 91%
See 2 more Smart Citations
“…This finding is not surprising as work demands had been previously found to influence information behavior (Ingwersen and Jarvelin, 2005;Vakkari, 2003;Yuelin and Belkin, 2008). In the context of professional reading, while many participants have adapted to reading digitally, the majority of them prefer to read longer professional documents in print, a preference prevalent in previous studies (Lopatovska et al, 2014;Zhang and Kudva, 2013;Woody et al, 2010).…”
Section: Effects Of Demographic and Institutional Characteristics On mentioning
confidence: 91%
“…In conjunction with this trend, the number of studies on information technology adoption in academia is also on the rise. Popular themes in technology adoption literature include information technology use, preferences of college students (Rod-Welch et al, 2013;Lopatovska et al, 2014;Foasberg, 2011) and faculty (Dodds et al, 2014;Mulholland and Bates, 2014) as well as issues pertaining to the development of digital collections and services (Dewan, 2012;Walters, 2013;Newman and Bui, 2010;Blummer, 2006). In an effort to understand the perspectives of those responsible for academic library offerings, several recent studies focussed on information behavior and technology use of academic librarians.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Features such as accessibility, credibility, coverage, cost, visual and interactive content, portability, and the easy-tonavigate interface attract users and enhance the circulation and usage of e-books 5 . The users also appreciate features of highlighting and adding annotations 6 . The features of adding annotations and sharing enhance users' engagement and leads to a rich learning experience 7 .…”
Section: Features Of E-books Which Attract Usersmentioning
confidence: 99%
“…In terms of use of electronic materials in reading, studies found that students tend to incorporate digital materials into their reading and prefer the use of digital materials over the printed alternatives. Also, it was revealed that the use of electronic paper varies between academic disciplines (Liu, 2006; Lopatovska et al, 2014; Savage et al, 2016). Another study by Kurata et al (2017) confirmed that reading electronic resources is predominant and has increased in the past 10 years.…”
Section: Academic Readingmentioning
confidence: 99%